Peningkatakan Keterampilan Belajar Melalui Penerapan Metode Pembelajaran Les Sore Di Desa Kaiwatu - Jecklin M. Lainsamputty; Inggrid N. Welerubun; Surlina F. Tuleta; Kundrat Luturmas; Yunita Rahanjaan; Thomas Melaira; Riska Awiara; Imelda M. Kay; Seli Y. Alerbitu; Maryana K. Udimera; Atalia Yermias; Charlota Matmey; Robeka M. Markus (Fakultas Teknik Universitas Cenderawasih, 2023)
This service aims to evaluate the effectiveness of implementing the Afternoon Tutoring learning method in improving student learning skills. This learning method is specifically designed to provide additional study time outside of regular class hours, with a focus on increasing understanding of material, application of concepts, and development of academic skills. Through a joint agreement between the school and Kaiwatu village, this program is run on Tuesdays and Saturdays from 4 pm to 6 pm. Of course, real work college (KKN) students are given the opportunity to apply every potential obtained in each field. studies. In rural education environments, challenges are often encountered such as lack of access to quality education, lack of motivation to learn, environmental factors that are less conducive, and less effective learning methods. The results obtained indicate that the application of the afternoon tutoring learning method is effective in increasing students' motivation and learning skills. These findings have positive implications for the development of learning strategies in rural areas with the hope of increasing achievement and reducing educational gaps.